Building a teaching module in a subject school theatre (Journal of the College of Basic Education, 2022)
The general development of life usually results in the need for a great deal of science in preparing a capable generationTo absorb the new tasks of life, and as Iraq witnessed development in all areas of life, zThe field of education has witnessed a great and clear development in its educational institutions, as education is no longer an issueConfined between the walls of schools and was not limited to classroom forms of education, but expandedThe learner has a prominent role in the educational process. He had to rely on himselfGain information and skills that help him in his practical life.And the traditional teaching methods achieve the relative stability that it has become receiving fromEducational institutions and educational circles However, what is happening is a continuous change in the environmentEducation and related matters and affects them, such as increasing the demand for learning and cognitive development